Polinização em genótipos de girassol (Helianthus annuus L.) - Chambó, Emerson Dechechi (2010)
The Research consisted of three experiments in Marechal Cândido Rondon city - PR, Brazil. In the first experiment the objective was to verify the influence of Apis Mellifera L. pollination on productive and physiological traits in sunflower achenes. The treatments were constituted by the combination of eight sunflower genotypes (Multissol, M734, Catissol 01, Charrua, MG2, Aguará, Helio 360 and Embrapa 122) and two tests of pollination, i) the flowers were free to insect visitation and ii) pollinators were restricted to visiting only inflorescences protected with gauze. The parameters analyzed were total productivity of seeds (PS), number of achenes per inflorescence (NA), mass of achenes per inflorescence (MA), mass of chapters (MC), chapter diameter (CD), ether extract in the achenes (EE), germination (GE), and mass of 1000 achenes (M1000). It was verified that the sunflower plants of the hybrid M734, exposed to insect pollination, showed PS and NA equal to 91,07% and 42,03%, respectively higher (p<0,05) than the plants of this hybrid with inflorescences protected with gauze. The chapters of the Catissol 01 cultivar exposed to insect pollination showed MA, MC and CD respectively, 150,52%, 130,28% e 35,06%, higher than the chapters of this cultivar protected with gauze. Inflorescences of the Embrapa 122 cultivar, free to insect visitation, presented EE and GE respectively, 52,63% e 134,29%, higher (p<0,05), than the inflorescences of this cultivar protected with gauze. Sunflower plants pollinated by Apis Mellifera presented average percentage of M1000 of 22,32% higher (p<0,05) than the plants protected with gauze, regardless of which genotype was being studied. In general, the pollination by insects enhances the productive traits and the quality of the seeds of sunflower genotypes. The second experiment was carried out with the objective of observing the type of food that africanized honey bees collect (pollen or nectar) at different times of day during the flowering period of five sunflower genotypes. The experimental design was arranged in randomized blocks split-plots scheme, with 100 treatments, four replications and two plants per experimental unit. The treatments were constituted by the combination of five genotypes of sunflower and (Helio 360, Helio 251, Charrua, Aguará e Multissol) allocated to plots and five days of observation and four time slots arranged in subplots. It could be seen that on the second and third days of sunflowers flowering there was a higher number of visits of Apis mellifera collecting nectar. It was observed that the honey bees collect pollen and nectar all they long, with peaks of collections from 7 to 8:30AM. The average density of honey bees throughout the day was 2.27 to 2.94 bees per inflorescence, and the honey bees collecting nectar were more frequent (2.28 bees / inflorescence) than honey bees collecting pollen (0.40 bees/inflorescence) on flowering days 2,94 and 2,96, respectively, and during the most visited time in the culture (7: 00 to 8:30 AM). On the third day of flowering, the hybrid Helio 360 and Aguará showed no differences amongst each other, and also showed higher (p <0.05) number of visitations of honey bees per inflorescence as compared to the other genotypes analyzed in the present study. It can be concluded that the africanized honey bees prefer to do their work of collecting food between the second and third day of flowering, between 7:00 to 8:30AM. Moreover, the hybrids Helio 360 and Aguará are more attractive to honeybees and should be recommended for maintenance and increase of number of pollinators in cultivated areas and to expand programs of honeybees pasture in the western of Paraná state, Brazil. The third experiment was carried out to evaluate the effect of the use of insecticide imidacloprid + beta-cyfluthrin on the number of visits by Apis mellifera bees to four sunflowers during the flowering season. Five plants were marked before the period of flowering of hybrids M734, Charrua, Helio 250 e Aguará, with four repetitions. Two observers remained two minutes on each plant, counting the number of honeybees in two intervals of time (from 8:30 AM to 10:00 AM and from 3:30 PM to 5:00 PM). The counting took place before the application of insecticide and twelve hours after the use of the product. It was verified that there was a significant negative effect of insecticide on the bees visitation considering the data of all hybrids, the hybrid of the M734 and Aguará. There was no effect of insecticide on the visit considering the data of the hybrid Charrua and Helio 250. It was also verified that the insecticide imidacloprid + beta-cyfluthrin causes repellence of Apis mellifera in sunflower crop. Moreover, the insecticide imidacloprid + beta-cyfluthrin was harmless to adults of Apis mellifera during blooming period for sunflowers, when applied to the lower middle third of the plants and the period in which these honeybees were not foraging. It would be necessary to assess their possible effects on young stages for further use in programs of integrated pest management in sunflower crop